Analysis of interference caused by air blocking valves in residential water meter measurements. Issue 1 (March 2021) - Trancoso, J; Cavaco, M; Kroth, J
Abstract: This work consists of an experimental study to better understand the interference of air block valves in measurements performed by metrological class 'B' velocity water meters. According to ordinance 'Portaria nº 246' from the National Institute of Metrology, Quality and Technology (Inmetro), the analysis was based on three experiments required for the approval of such equipment: Errors measurement, Head loss measurement and Magnetic transmission efficiency test. In order to collect the results an automated bench was developed enabling experiments execution without human intervention. Data acquired showed non-compliance with regulation when the system operated with the device. The conclusion taken by the results indicates that the specific air block valve tested may be a harmful influence on the correct operation of water meters.